1998
DOI: 10.1352/0047-6765(1998)036<0465:cacipr>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Confirmed Abuse Cases in Public Residential Facilities for Persons With Mental Retardation: A Multi-State Study

Abstract: Data regarding cases of confirmed abuse or neglect in large state-operated facilities in 6 states were collected and analyzed. Neglect and physical abuse were the most common abuse types. Incidents occurred more frequently on the afternoon-early evening shift, particularly between 3 and 6 p.m., and more frequently in residential than in nonresidential areas. In-transit activities were found to be relatively risky. The major risk factors for victims were maladaptive behavior and previous abuse victimization. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 0 publications
0
28
0
Order By: Relevance
“…Literature on institutional abuse frequently includes groups of people that are in need of care like those within a psychiatric institution [29] or within institutional care for the elderly [30]. It is commonly characterized “by the systemic destruction of a person’s self-esteem through psychologically abusive tactics” [31].…”
Section: Discussionmentioning
confidence: 99%
“…Literature on institutional abuse frequently includes groups of people that are in need of care like those within a psychiatric institution [29] or within institutional care for the elderly [30]. It is commonly characterized “by the systemic destruction of a person’s self-esteem through psychologically abusive tactics” [31].…”
Section: Discussionmentioning
confidence: 99%
“…While these studies do not enable estimates of the proportion of people with ID who experience maltreatment, they provide valuable information regarding the strength of the association between disability and maltreatment. Other studies [Doren et al, 1996;McCartney and Campbell, 1998] have examined individual and environmental predictors of maltreatment, thereby elucidating points at which interventions are most critical. Still others [Lumley et al, 1998;Miltenberger et al, 1999;Khemka and Hickson, 2000;Khemka et al, 2005] have focused on evaluating prevention efforts.…”
Section: Reflections and Recommendationsmentioning
confidence: 99%
“…Other research has focused on abuse in particular situations – for example, Baker & Allen (2001) consider what is needed to prevent physical abuse associated with the use of physical interventions for people with challenging behaviour. McCartney & Campbell (1998) analysed the 494 confirmed cases of neglect and abuse in public residential facilities for people with intellectual disabilities across six US states and across a 22‐month period. They found that neglect was the most common type of abuse, followed by physical aggression (together accounting for over 80% of all cases).…”
Section: Introductionmentioning
confidence: 99%